Perbandingan Metode SAW, MAUT, ORESTE, TOPSIS dalam Pendukung Keputusan Pembangunan Supermarket di Kabupaten Pati - Dewasasmita, Elsha Yuandini; Hendry, H (STIKOM Tunas Bangsa Pematangsiantar, 2023)
This study aims to find out the best sub-districts in Pati Regency which are located outside Pati District as a place for Supermarket construction based on the specified criteria and a comparison of the four methods to be used. The tool used to support this research process is Microsoft Excel. This study uses the SAW, MAUT, ORESTE, and TOPSIS methods in the research model to compare the final results. The final results obtained are that the SAW and TOPSIS methods have the first three orders, namely A10, A15, and A3, the MAUT method has the same first three orders, namely A10, A3, and A15, while the ORESTE method has the first three orders, namely A21, A10, and A3. By looking at the opportunities for emergence, the final results show A10, namely Kayen District as the best sub-district in supporting supermarket development decisions in Pati Regency.